Development Accounting: Lessons for Latin America - Daude, Christian (OECD Development Centre Working Papers, 2012)
This paper presents development accounting exercises in Latin America using novel databases and methods to investigate the robustness of its results. While total factor productivity initially appears to be the most important driver of output per worker gaps in Latin America and the Caribbean, this "fact" is not robust to alternative functional forms, adjustments for the quality of human capital and endogeneity considerations. The paper also highlights the heterogeneity among countries in the region and discusses alternative ways to link macroeconomic benchmarking to policies